Cultural Economy and Television in Jamaica and Ghana: #decolonization2point0 - Hickling Gordon, Deborah (Palgrave Pivot, 2020)
This book proposes contemporary decolonization as an approach to developing cultural economies in the Global South. This book represents the first critical examination and comparison of cultural and creative industries (CCI) and economy concepts in the Caribbean and Africa.
Keywords: 1-TV; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Ghana (corpus analysé); Jamaïque (corpus analysé); Jamaïque (lieu de production du savoir); _Nettoyé